Effect of Amomum villosum essential oil as an additive on the chemical composition, fermentation quality, and bacterial community of paper mulberry silage - Li, Maoya; Fan, Xueying; Cheng, Qiming; Chen, Yulian; Long, Jianhua; Lei, Yao; Li, Ping; Chen, Chao (Frontiers in Microbiology, 2022)
Paper mulberry (Broussonetia papyrifera L., PM) is being used as a new type of animal protein feed to address the feed crisis. To investigate the effect of additives on the chemical composition, fermentation quality, and bacterial community of PM silage (at room temperature, 25°), paper mulberry was fermented with formic acid (FA), Amomum villosum essential oil (AVEO) and lactic acid bacteria (LAB) inoculant treatments. The results showed that fresh PM had a low water-soluble carbohydrate content and large amounts of unclassified bacteria. Compared with the CK and LAB treatments, the FA and AVEO treatments significantly (P < 0.05) decreased the pH and increased the lactic acid content of PM silage after 60 days of ensiling. In the AVEO-treated silages the abundance of Lactococcus in the early stage of ensiling increased by 14.09%, the abundances of Levilactobacillus and Lentilactobacillus in the late stage of ensiling increased by 58.34 and 91.12%, respectively, and the abundance of Stenotrophomonas decreased by 94.71%, resulting in improved PM silage quality. These results confirmed that AVEO could potentially be developed as a new additive for improving the fermentation quality of silage.